Early onset familial relapsing polyneuropathy, mimicking CIDP; A lesson from clinical genetics - saadi, nebal wael (Journal of the Faculty of Medicine Baghdad, 2021)
Background: In children, chronic immune-mediated neuropathies present with slowly progressive or relapsing episodes of gait difficulty, symmetric weakness and sometimes paraesthesia. Infancy and early childhood age of presentation and familial recurrence are believed to be atypical features.Case presentation: Herein, we describe two brothers from a non- consanguineous Iraqi family, who presented with episodes of acute immune-mediated demyelinating peripheral neuropathy in early infancy that relapsed recurrently. Mild haemolytic anaemia was also reported. Inherited metabolic disorders were suspected and Whole Exome Sequencing of the youngest brother revealed homozygous frame shift mutation in CD59 gene, confirming the diagnosis of autosomal recessive hemolytic anemia, CD59-mediated, with or without immune-mediated polyneuropathy (HACD59).Conclusion: The report highlights the advantage of genetic testing in such rare and inherited conditions. In the lack of necessary non-traditional diagnostic methods, it is substantial to maintain the accustomed medical practice and strategies, based on available clinical data.